2021
DOI: 10.1272/jnms.jnms.2021_88-101
|View full text |Cite
|
Sign up to set email alerts
|

Association of Pedicle Sign Type with Clinical and Radiological Features in Patients with Symptomatic Spinal Metastases

Abstract: Background: Cancer diagnoses are increasing rapidly due to the aging population of Japan. Pedicle sign is a valuable radiographic indicator of metastases as the pedicle is the most commonly affected part of the vertebra upon radiographic assessment. However, few detailed studies examining the morphological features of pedicle signs have been performed. To improve the capacity of medical professionals to diagnose symptomatic spinal metastases, we retrospectively examined the morphological characteristics of ped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…The first half of this study has already been reported for patients with a positive pedicle sign 5 . This report is the second half of the study, examined patients with negative pedicle signs.…”
Section: Methodsmentioning
confidence: 83%
See 4 more Smart Citations
“…The first half of this study has already been reported for patients with a positive pedicle sign 5 . This report is the second half of the study, examined patients with negative pedicle signs.…”
Section: Methodsmentioning
confidence: 83%
“…The clinical characteristics of the BCP and BCN groups are summarized in Tables 1 and 2. Primary cancer sites included the lung (24), prostate (5), kidney (3), breast (4), digestive system (9), hematopoietic system (11), and others (8). The sites evaluated included 3 cervical, 24 thoracic, and 37 lumbar vertebrae.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations